CAMPUR KODE PADA INTERAKSI MASYARAKAT DESA BANJARSARI KECAMATAN SUKATANI, KABUPATEN BEKASI: KAJIAN SOSIOLINGUISTIK - Hasanah, Nisrina; Wagiati; Wahya (Universitas Hamzanwadi, 2025)
Bekasi was and still an area with many social contacts of various languages because Bekasi had a port that is the center of traders meeting from various regions. Due to that influence of various languages, Bekasi residents sometimes mix various local languages ​​when speaking. Therefore, the purpose of this study is to determine the code mixing that occurs in Banjarsari Village, Sukatani District, Bekasi Regency and what factors influence the occurrence of code mixing there. The method used is qualitative descriptive method. The data were collected using the listening method with tapping and recording techniques. We recorded the interactions of residents in two domains, namely neighborhood and transactions then analyzed it using the padan method with the Hubung Banding Menyamakan, Hubung Banding Membedakan, and Hubung Banding Menyamakan Hal Pokok techniques. The data were also analyzed using the code mixing theory by Muysken which is insertion, alternation, and congruent lexicalization. The data are presented using formal and informal methods. In Banjarsari Village, code mixing occurs in four languages, namely Banten Javanese, Betawi, Sundanese and Indonesian. This code mixing occurs due to the history of politics and territory, intermarriage, social media, and speakers who come from outside the village.